PHOTOVOLTAIC POWER PLANT OUTPUT POWER ENHANCEMENT DESIGN WITH SOLAR TRACKER - Sadhana, Agya
The purpose of this study is to design and implement a scheduled PV Power Plant Single-axis Solar Tracker that will be realized using Arduino. This design takes into account the performance of 3 alternative solutions by using the NASA-SSE satellite database for stand-alone solar cells installed in front of the Conversion Lab Building with standard household loads (refrigerators, lights, TVs, electric stoves). After experimenting with the tool and re-simulating all alternative solutions, 3 alternative solutions were obtained that need to be further explored, namely fixed tilt, continuous tracking, and scheduled tracking. It can be concluded that by utilizing the two features of conventional tracking ideas, namely single-axis and timer-based tracking, this study shows that the design of the PV hybrid tracking solution in terms of assessment matrix, has significant advantages in terms of efficiency and power consumption compared to fixed tilt, continuous tracking, and scheduled tracking designs. With an average yield of 5.59 Wh/h and a motor energy consumption of only 62.77 mWh, the hybrid design has a yield that is only 0.36% lower than the continuous tracking which reaches 5.61 Wh/h. However, the energy consumption of the motor in the hybrid design is 64.2% lower than continuous tracking which requires 175.22 mWh, and only 43.3% higher than scheduled tracking which requires 43.81 mWh. The additional components required are also minimal, so they do not significantly burden the cost and complexity of the circuit.